Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.4 The Product and Quotient Rules - 3.4 Exercises: 32

Answer

$y' = 1$

Work Step by Step

Quotient Rule: $y=\frac{x^2-2ax+a^2}{x-a}$ $y' = \frac{(2x-2a)(x-a)-(x^2-2ax+a^2)(1)}{(x-a)^2} = 1$ Division then Power Rule: $y=\frac{x^2-2ax+a^2}{x-a}=\frac{(x-a)^2}{x-a} = x-a$ $y' = 1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.